Seasonal prevalence of fasciola gigantica infection among the sexes in Nigerian Cattle (2008)
This study examined the seasonal prevalence of fasciolosis between tire sexes in Nigerian cattle. The possible role and effect of sex on prevalence of the disease is also discussed. One thousand cattle were examined for infection using the fecal and bile examination for Fasciola eggs and Agar gel precipitation test. Total 750 75%), 448 (44.8%) and 450 (45%) positive were detected by each of tire three methods respectively. The first peak of infection was detected in February' and the second from September to October. Prevalence was higher (52.3%) during the rainy seasons. The annual prevalence was higher in females (63.7%) than in males (36.3%). Prevalence was also higher in females from December to September and peaked (8.1%) in February. Peak prevalence for males occurred in September and October (6.6%), overall prevalence was found to be higher in the females and statistically significant during the dry season.